Precise chemodynamic therapy of cancer by trifunctional bacterium-based nanozymes - Zhang, Weiyun (2022)
Chemodynamic therapy (CDT) destroys cancer cells by converting H2O2 or O2 into reactive oxygen species (ROS), but its therapeutic efficacy is restricted by the antioxidant capacity of tumor. Previous solutions focused on strengthening the nanodrugs with the ability to increase ROS production or weaken the antioxidant capacity of cancer cells. Conversely, we here develop a mild nanodrug with negligible side effects. Specifically, the Au@Pt nanozyme decorated on a bacterial surface (Bac-Au@Pt) is reported to achieve precise CDT. Due to the tumor targeting ability of bacteria and catalytic property of Au@Pt nanozyme under acidic conditions, this nanosystem can release ROS to tumor cells effectively. In addition, the interferon gamma released by T cells specifically decreases the intracellular reductants in tumor cells, while having no obvious effect on normal cells. Therefore, a low dose of Bac-Au@Pt achieves a satisfactory therapeutic efficacy to tumor cells and is nontoxic to normal cells even at their acidic components. This nanosystem enables CDT and immunotherapy to mutually benefit and improve by each other, providing a promising strategy to achieve high anticancer efficacy even with a low dose usage.